Path Analysis of the Work Environment and Motivation on Loyalty with Job Satisfaction as Intervening Variables - Rhendy Akhmad Firdaus; Popy Navita Pasaribu (University of Merdeka Malang, 2023)
Today's business competition requires organizations to be able to have employees who can be competitive in all fields, motivation and a comfortable work environment can be factors that can lead to loyalty to job satisfaction in order to achieve organizational goals. The method of this study is purposive sample and data collection by distributing questionnaires to several government agencies and private institutions. We analyzed with quantitatively using the test of validity, reliability and the path analysis method. The research show all of the item of question is valid and show that there is a direct significant effect of work environment and motivation on job satisfaction; directly there is no significant effect of the Work Environment on Loyalty; there is a direct significant effect of motivation on loyalty; there is a direct significant effect of job satisfaction on loyalty; indirectly the work environment through job satisfaction has a significant influence on loyalty and indirectly motivation through job satisfaction has a significant influence on work loyalty.